Two new species, two rediscoveries and a range extension in Lachenalia (Asparagaceae: Scilloideae) from southern and western South Africa - Duncan, Graham (Phytotaxa, 2017)
Two recently discovered species of Lachenalia from South Africa, Lachenalia barbarae from the Overberg district of the Western Cape and Lachenalia adamii from the Bokkeveld escarpment of the Northern Cape, are described. In addition, details of the rediscovery of two species previously thought to be possibly extinct in the wild, Lachenalia martleyi from the Overberg district in the Western Cape and Lachenalia macgregoriorum from the Bokkeveld plateau in the Northern Cape, are provided, as well as a range extension for the critically endangered Lachenalia moniliformis from the Breede River Valley in the Western Cape.